Epalrestat Improves Diabetic Wound Healing via Increased Expression of Nerve Growth Factor - Nakagaki, O.; Miyoshi, H.; Sawada, T.; Atsumi, T.; Kondo, T.; Atsumi, T. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Aldose reductase inhibitors (ARIs) are a useful therapy for diabetic neuropathy. Nerve damage is associated with delayed wound healing of skin ulcers in diabetic patients. Therefore, we hypothesized that ARI supplementation would improve diabetic wound healing.Control and streptozotocin-induced diabetic mice were fed either control diet or diet containing the ARI Epalrestat (40 mg/kg). After 12 weeks, we created skin wounds on the backs of the mice. Wound healing was determined by measuring the reduction in wound area.The wound gap of the diabetic group was significantly larger 9 days after creating the wounds when compared to the other groups (p<0.01). Interestingly, wound healing in the diabetic mice fed Epalrestat was comparable to the non-diabetic mice. To clarify the mechanism(s) behind this improved wound healing, mRNA expression of growth factors reported to be involved in wound healing were examined. Among the growth factors investigated, only the expression of nerve growth factor (NGF) was significantly decreased (54.0%) in the healing lesions of diabetic mice. Similarly, NGF protein expression was decreased in diabetic mice and recovered in Epalrestat treated diabetic mice. Inhibition of NGF via 2 separate inhibitors (K252a and BSO) reduced the ability of Epalrestat to improve wound healing in diabetic mice.These findings suggest that Epalrestat is a potential therapy for improving diabetic wound healing and the mechanism involves upregulation of NGF.
Keywords: aldose reductase inhibitor; wound healing; nerve growth factor